URGENTLY-NEEDED: STUDENT-FRIENDY LEARNING RESOURCES ON ATOMIC STRUCTURE AND PERIODICAL PROPERTIES OF ELEMENTS - Monica Prima Sari (SEMESTA: Journal of Science Education and Teaching, 2020)
This study aimed to figure out what kind of learning resources that science students-teacher used at Basic Inorganic Chemistry Course, especially for the topic of Atomic Structure and Periodical Properties of elements, given the fact that they have studied these topics twice: in Chemistry subject at senior high school and in the second semester at the university. The main background of this study was students’ grades at the end of the semester which was still not living up to the expectation. We believed there could be several factors behind this result. However in this study, we focused on one factor: learning resources. A survey was conducted to figure out: 1) what kind of learning resources that students use; and 2) what are the characteristics of learning resources students expect to have to help them in this course. The data was then analyzed with descriptive statistics technique. Our discussion expanded to the existing learning resources that students can access and what we could offer to help narrowing the gap.